Pengembangan Media Arabic Alphabet for Kids untuk Pengenalan Huruf Hijaiyah (PIAUD IAIN Kudus, 2021)
The implementation of learning the introduction of Hijaiyah letters at RA Miftahul Ulum, Cirebon Regency has not been effective so that researchers develop learning media to improve the ability to recognize Hijaiyah letters in the form of Arabic Alphabet for Kids. This study uses the Research and Development method using data collection techniques in the form of questionnaires, observations, interviews, and documentation. This research was held for about 6 months The type of data analysis produced is a descriptive qualitative analysis using percentage calculations. This study resulted in a product in the form of Arabic Alphabet for Kids media which was declared suitable to be used for the introduction of children’s Hijaiyah letters. Expert judgment for media resulted in 100% and material expert validation obtained 96, 42% results, user assessments conducted by class A teachers obtained 91.66% results, and user assessments carried out by class B teachers. obtained a yield of 93.75%. In addition, during the media trial, children’s ability to recognize Hijaiyah letters increased to 77.81% which was included in the very well-developed category (BSB).